Auditando en las bases de datos (ING) - Villalobos Murillo, Johnny (2008)
The importance of establishing controls that allow you to diminish the inherent risk that has the data contained in a database make necessary implement audit procedures. Two types of audits applicable to the database exist essentially, the audit of object and the audit of transactions, some system database manager provide mechanisms for the first type, whereas to make the audits of transaction, is necessary to create our own procedures or to go to solution of third.